2021
DOI: 10.3390/biology10060495
|View full text |Cite
|
Sign up to set email alerts
|

Harvest Season Significantly Influences the Fatty Acid Composition of Bee Pollen

Abstract: Seasonal variations in the fatty acid (FA) compositions of pollen loads collected from the Al-Ahsa Oasis in eastern Saudi Arabia throughout one year were determined to identify the optimal season for harvesting bee pollen rich in essential fatty acids (EFAs) and unsaturated fatty acids (UFAs). The highest values (%) of lipids, linolenic acid (C18:3), stearic acid (C18:0), linoleic acid (C18:2), arachidic acid (C20:0), the sum of the C18:0, C18:1, C18:2, and C18:3 concentrations, and EFAs were obtained from bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
2
12
0
1
Order By: Relevance
“…MUFA content was found to be higher than SFA content in all seasons. Similar to this result, MUFA content was higher than SFA in MBP oil samples except for the UAE-H. [49] Studies have reported that oleic and palmitic acids are the predominant fatty acids in the bodies of larval and adult honeybees, and feeding bee pollen rich in these fatty acids has a critical effect on honeybee development. [44] Therefore, it was thought that MBP could be recommended for honeybee colony nutrition with its significant content of palmitic and oleic acids, especially palmitic acid.…”
Section: Fatty Acid Content Of Oil Extractssupporting
confidence: 80%
“…MUFA content was found to be higher than SFA content in all seasons. Similar to this result, MUFA content was higher than SFA in MBP oil samples except for the UAE-H. [49] Studies have reported that oleic and palmitic acids are the predominant fatty acids in the bodies of larval and adult honeybees, and feeding bee pollen rich in these fatty acids has a critical effect on honeybee development. [44] Therefore, it was thought that MBP could be recommended for honeybee colony nutrition with its significant content of palmitic and oleic acids, especially palmitic acid.…”
Section: Fatty Acid Content Of Oil Extractssupporting
confidence: 80%
“…From the data presented, in the samples analyzed in our study, the most abundant essential amino acids were histidine (values of 0.29–2.30 µg/mg), lysine (0.14–0.74 µg/mg) and phenylalanine (0.12–0.43 µg/mg). Histidine was found to predominate in the bee pollen collected during autumn, while high levels of lysine and phenylalanine were determined in bee pollen collected during winter [ 50 ]. The distribution of these essential amino acids in the analyzed bee pollen was therefore in accordance with the period when the samples were collected.…”
Section: Resultsmentioning
confidence: 99%
“…When studying the fatty acids profile of bee pollen, the ratio between UFA and SFA is of great importance. It was considered that a value of the UFA/SFA ratio higher than 1 is characteristic of bee pollen with considerable nutritional value, while a value below 1 indicates degradation of unsaturated fatty acids due to storage and dehydration process [ 50 ]. For the 24 bee pollen samples analyzed in our study, the UFA/SFA ratio varied between 1.86 and 5.78 and was comparable with the values of 2.2–6.7 reported for the bee pollen from India [ 27 ] and the 1.9–2.2 UFA/SFA ratio calculated for commercial bee pollen from Colombia, Italy and Spain [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other fatty acids such as oleic acid and myristic acid have also been reported as the main lipidic components [ 43 ]. The storage conditions [ 66 ], manipulation and processing of BP may alter its lipidic profile. Drying with different techniques, for example, which is the most common operation in pollen use by humans, was shown to reduce its lipid content and alter the structure of its fatty acids, with freeze-drying having the least impact [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, harvesting season was also reported to significantly influence lipid profile. An analysis of pollen loads harvested around one year in the same geographic location showed that, not only did the percentage of different fatty acids in the total lipids vary according to the period of collection, but also that the ratio of unsaturated to total fatty acids was variable during the year with a maximum registered in the summer period [ 66 ].…”
Section: Resultsmentioning
confidence: 99%